1999
DOI: 10.1007/s00585-999-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

Observations of polar patches generated by solar wind Alfvén wave coupling to the dayside magnetosphere

Abstract: Abstract. A long series of polar patches was observed by ionosondes and an all-sky imager during a disturbed period (K p 7-and IMF B z < 0). The ionosondes measured electron densities of up to 9´10 11 m A3 in the patch center, an increase above the density minimum between patches by a factor of $4.5. Bands of F-region irregularities generated at the equatorward edge of the patches were tracked by HF radars. The backscatter bands were swept northward and eastward across the polar cap in a fan-like formation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 95 publications
3
36
0
Order By: Relevance
“…Early studies estimated the typical recurrence time between bursts as being *7-8 mins Provan et al 1998) closely matching what had been identified as the average recurrence time for magnetopause FTEs (Rijnbeek et al 1984;Lockwood and Wild 1993). Prikryl et al (1998Prikryl et al ( , 1999Prikryl et al ( , 2002 presented observations that implied that, at times, quasi-periodic ionospheric flow bursts were correlated with Alfvénic fluctuations observed in the upstream solar wind, with similar waveforms being observed in the IMF, in the magnetosheath, and in ionospheric convection flows. They suggested that compressional MHD waves in the solar wind were responsible for driving compressional waves in the magnetosphere, and further suggested that these ULF waves modulated reconnection at the dayside magnetopause into pulses, hence the correlated periodicity.…”
Section: The Structure and Dynamics Of Mesoscale Convectionsupporting
confidence: 55%
See 1 more Smart Citation
“…Early studies estimated the typical recurrence time between bursts as being *7-8 mins Provan et al 1998) closely matching what had been identified as the average recurrence time for magnetopause FTEs (Rijnbeek et al 1984;Lockwood and Wild 1993). Prikryl et al (1998Prikryl et al ( , 1999Prikryl et al ( , 2002 presented observations that implied that, at times, quasi-periodic ionospheric flow bursts were correlated with Alfvénic fluctuations observed in the upstream solar wind, with similar waveforms being observed in the IMF, in the magnetosheath, and in ionospheric convection flows. They suggested that compressional MHD waves in the solar wind were responsible for driving compressional waves in the magnetosphere, and further suggested that these ULF waves modulated reconnection at the dayside magnetopause into pulses, hence the correlated periodicity.…”
Section: The Structure and Dynamics Of Mesoscale Convectionsupporting
confidence: 55%
“…However, there have been attempts to characterize this 2-D signature. Although not making 2-D observations, Prikryl et al (1999) suggested that the Wild et al (2003), copyright by the European Geophysical Union Surv Geophys (2007) 28:33-109 49 ionospheric flow bursts could be associated with poleward progressing DPY currents (Hall currents modulated by variations in IMF B y ). Many of the recent SuperDARN 2-D observations of dayside flow transients appear to fit with a simple picture of polewardmoving FAC systems which are associated with PMAFs, poleward-moving local convection reversals, and other poleward-moving velocity structures (Chisham et al 2000b;Thorolfsson et al 2000;Lockwood et al 2001).…”
Section: The Structure and Dynamics Of Mesoscale Convectionmentioning
confidence: 99%
“…This is consistent with expectation of largely precipitation-driven auroral irregularities and convection-driven cusp irregularities. In the cusp, L-shell aligned flow channel events frequently shape the density structure by producing density depletions with steep gradients perpendicularly to L-shell (Rodger et al, 1994;Prikryl et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Under the conditions of IMF B y > 0, the SuperDARN convection maps (Fig. 4) showed quasi-periodic dayside ionospheric convection enhancements (westward flow channels) as a response to solar wind coupling at the magnetopause (Prikryl et al, 1999; see their Fig. 1).…”
Section: Instruments and Datamentioning
confidence: 95%
“…Similar observations have been made by Kepko et al (2002) relating oscillations in the solar wind to pulsations at geosynchronous orbit. Other authors (Potemra et al, 1989;Shimazu et al, 1995;Prikryl et al, 1998Prikryl et al, , 1999 have also reported ground-based observations of quasi-periodic phenomena associated with solar wind oscillations. There have also been observations of surface waves on the magnetopause correlated with solar wind oscillations at discrete frequencies (Sibeck, 1992).…”
Section: Introductionmentioning
confidence: 97%